Test Instruments to Measure Non-Routine Mathematics Problem Solving Ability Grade IV Elementary School Students - Jatiningtyas, Parwati Dewi; Kartono; Mindyarto, Budi Naini (Journal of Education Reseach and Evaluation, 2022)
Teachers have a very vital role in the availability of quality education. Various classroom practices used in interacting with students play an important role in understanding mathematical concepts and overall performance in mathematics. This study aims to produce a prototype of a valid and reliable mathematical test instrument for fourth grade elementary school students. This research is a development research. Item analysis of the test instrument using the Rasch model includes ten steps of research and development implementation strategy. Research respondents consist of 5 people on the expert test, 28 people on the small-scale test, and 86 people on the large-scale test. Data was collected by using interview, documentation and questionnaire techniques. Analysis conducted through quantitative and qualitative data. This test prototype development instrument produces a complete Mathematics test. The reliability tested includes inter-rater reliability, namely 0.613, Cronbach Alpha reliability for small- scale tests 0.81 and large-scale test results on Cronbach Alpha reliability 0.78. Based on the results of research and discussion, it can be concluded that the mathematical test instrument to measure non- routine problem solving skills developed is valid and reliable. Existing instruments can help teachers to assess the mathematics ability of fourth grade elementary school students.